Differences in pre-planned agility and reactive agility performance in sport games - Simonek, J.; Horicka, P.; Hianik, J. (Acta Gymnica, 2016)
Background: Authors in their contribution point to the differences in the methods of measurement of agility in the practice. Based on the experience of coaches as well as on their own experience have come to the conclusion that the Illinois Agility Test, which has long been used for the testing of agility in fact does not measure perception abilities and decision-making processes, since motor activity performed during the testing procedure represents a closed skill, where the only task of the tested person is to accelerate, decelerate and change the direction of running, while the task is known in advance. On the contrary, some authors recommend the testing of agility using apparatuses measuring selective reaction, such as Fitro Agility Check.